Сalprotectin in the blood plasma as a new biomarker for assessing the activity of rheumatoid arthritis - A. A. Korolkova; V. V. Khizha; D. I. Kozlova; A. L. Maslyanskiy; T. V. Vavilova (Бюллетень сибирской медицины)
Aim. To study the potential use and information value of calprotectin in the blood plasma as a new biomarker for determining the activity of rheumatoid arthritis (RA).Materials and methods. The study included 113 people. The treatment group consisted of 79 patients diagnosed with RA; the average age was 58 (± 11.66) years, the median duration of the disease was 10 [6; 15] years. The control group encompassed 34 healthy volunteers; the average age was 40 (± 11.14) years. RA activity was determined according to the Disease Activity Score (DAS) 28 and the Clinical Disease Activity Index (CDAI). The concentration of calprotectin in the blood plasma was determined by the solid-phase enzyme-linked immunosorbent assay. The obtained results were compared with laboratory and clinical parameters, as well as with composite indices (DAS28, CDAI) of RA activity. For mathematical data processing, Spearman’s rank correlation coefficient, linear discriminant analysis, and ROC analysis were used.Results. In the group of patients with RA, the level of calprotectin in the blood was higher than in the control group. A statistically significant relationship was revealed between the level of calprotectin in the blood and all standard parameters of RA activity. The ROC analysis showed that the sensitivity, specificity, and diagnostic accuracy in assessing articular syndrome, as well as moderate and high RA activity according to the composite indices DAS28 and CDAI were higher for calprotectin than for erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). The linear discriminant analysis showed that a combination of ESR and calprotectin levels was the most informative; following it, the probability of correct classification of RA activity, according to the DAS28 index, was 71%. For the CDAI index, only one marker, calprotectin, resulted in a statistically significant classification with a probability of 70.5 %.Conclusion. Сalprotectin in the blood plasma is a promising laboratory biomarker for assessing synovitis activity in RA demonstrating higher accuracy, sensitivity, and specificity than traditional acute-phase reactants.